Medications for the treatment of pulmonary arterial hypertension: a systematic review and network meta-analysis. (10th August 2022) - Pitre, Tyler; Su, Johnny; Cui, Sonya; Scanlan, Ryan; Chiang, Christopher; Husnudinov, Renata; Khalid, Muhammad Faran; Khan, Nadia; Leung, Gareth; Mikhail, David; Saadat, Pakeezah; Shahid, Shaneela; et al.
Background: There is no consensus on the most effective treatments of pulmonary arterial hypertension (PAH). Our objective was to compare effects of medications for PAH. Methods: We searched MEDLINE, Embase, the Cochrane Central Register of Controlled Trials andClinicaltrials.gov from inception to December 2021. We performed a frequentist random-effects network meta-analysis on all included trials. We rated the certainty of the evidence using the Grades of Recommendation, Assessment, Development, and Evaluation approach. Results: We included 53 randomised controlled trials with 10 670 patients. Combination therapy with endothelin receptor antagonist (ERA) plus phosphodiesterase-5 inhibitors (PDE5i) reduced clinical worsening (120.7 fewer events per 1000, 95% CI 136.8–93.4 fewer; high certainty) and was superior to either ERA or PDE5i alone, both of which reduced clinical worsening, as did riociguat monotherapy (all high certainty). PDE5i (24.9 fewer deaths per 1000, 95% CI 35.2 fewer to 2.1 more); intravenous/subcutaneous prostanoids (18.3 fewer deaths per 1000, 95% CI 28.6 fewer deaths to 0) and riociguat (29.1 fewer deaths per 1000, 95% CI 38.6 fewer to 8.7 more) probably reduce mortality as compared to placebo (all moderate certainty). Combination therapy with ERA+PDE5i (49.9 m, 95% CI 25.9–73.8 m) and riociguat (49.5 m, 95% CI 17.3–81.7 m) probably increase 6-min walk distance as compared to placebo (moderate certainty). Conclusion: Current PAH treatments improve clinically important outcomes, although the degree and certainty of benefit vary between treatments. Combination therapy with PDE5i plus ERA and riociguat monotherapy were most effective at reducing clinical worsening and improving 6MWD in PAH. https://bit.ly/3xlZqDF